Photochemistry in CuInS2 Quantum Dots/Polyoxometalate System - Azzah Dyah Pramata; Tetsuya Kida (IPTEK Journal of Proceedings Series, 2015)
Energy transfer involving semiconductor quantum dots (QDs) has received increased attention in recent years because of high photostability and size-tunable optical properties. Here, we study photochemistry in quantum dot/polyoxometalate (POMs) systems and utilize quantum dots as light antenna that captures visible light to sensitize wide band gap POMs. We also demonstrate the photoenergy storage properties of CuInS2 QD/POM systems. The PL quenching and the decrease in PL lifetime are clear indication that the excited electron of CuInS2 was deactivated by electron transfer to POM such as PMo12O40, W10O32 and SiW10O36 that were hybridized with a cationic surfactant and dispersed together in an organic solvent. The quantum yields of CuInS2 QDs were 2.32% with 3.9 nm in particle size. Irradiating QD/POM systems with visible light generates a one-electron reduced form of POMs, suggesting the reduction of POMs. Photoenergy can be stored as reduced POM under deaerated conditions by visible light. Stored electron in POM can be discharged afterwards via reductive reactions such as oxygen under the dark.